Ecology of hermit crabs (family diogenidae) in Matang mangrove estuary and adjacent coastal waters / Teoh Hong Wooi - Teoh, Hong Wooi (2014)
Ecological aspects of diogenid hermit crabs were studied in Matang mangrove estuary and adjacent coastal waters to determine their abundance and distribution in relation to abiotic and biotic factors, population dynamics, shell use patterns, reproduction and trophodynamics. Samplings of hermit crabs and environmental parameters were carried out at mid-estuary, river mouth, coastal mudflat and offshore shoal waters, using a small otter trawl from August 2009 to March 2011. The major hermit crab species were D. lopochir Morgan, 1989, Diogenes moosai Rahayu & Forest, 1995, and Clibanarius infraspinatus Hilgendorf, 1869 which dominated the shoal area, mudflat and mid-estuary, respectively. The growth (K) and total mortality (Z) rates of D. moosai and D. lopochir, as fitted by the von Bertalanffy growth function were 1.4, 7.06 and 1.3, 3.54, respectively. Both Diogenes species reproduced mainly in January/February and July which resulted in one major and one minor recruitment pulse in a year. The two sympatric species of Diogenes adopted different reproduction strategies. D. moosai, at higher risk of exposure to extreme physical conditions in the mudflat, generally spreads its reproduction over the year (continuous reproduction), while D. lopochir, at greater risk of predation in the subtidal shoal area reproduces at the most favourable period (discontinuous reproduction). The availability of gastropod shells is an important biotic factor modulating the distribution and abundance of hermit crabs, since empty shells were few and broken shells were occupied. Shells of 14 gastropod species were used by both Diogenes species, but >85% comprised shells of mainly four species, Cerithidea cingulata, Nassarius cf. olivaceus, N. jacksonianus and Thais malayensis. Extreme bias in shell use pattern by male and female of both Diogenes species suggests that size compatibility between hermit crab and shell determines the shell use pattern and explains ecological partitioning between species and sex of hermit crabs. Where their distribution overlaps in offshore waters, interspecific competition between D. moosai and D. lopochir is hypothesized to be modulated by predation thus allowing coexistence. Stable isotope analysis revealed the dependency of Diogenes hermit crabs on microphytobenthos (49.9%±14.6%) as their major primary source of nutrition, followed by phytoplankton (27.6%±9.3%) and mangrove (22.5%±7.7%). Hermit crabs serve as prey organisms to predatory fishes indicating the intermediary role played by hermit crabs (2nd and 3rd trophic level) in the food web of the Matang ecosystem.